Job autonomy and work-life conflict: A conceptual analysis of teachers’ wellbeing during COVID-19 pandemic - Khawand, Sonia; Zargar, Pouya (Frontiers in Psychology, 2022)
With the shift towards online environments due to COVID-19 pandemic, particularly for educational sector, employees’ performance has been affected by an array of different factors. Personal aspects as well as organizational focus on individuals’ wellbeing are the main focus of this study through inclusion of job autonomy, work-life conflict alongside other factors such as, informational support that can aid academic staff regarding their wellbeing during times of crisis. In response to the effects of COVID-19 on employees, this study aims to provide tangible data to protect university teachers during crises and establish key points that can improve their wellbeing. For this purpose, we used interviews to provide in-depth understanding on the subject. A total of 16 teachers as interviewees have provided qualitative data that was analyzed with MAXQDA (thematic network approach). This study highlights the importance of work-life conflict and vitality of job autonomy on academic staffs’ performance and overall wellbeing through a conceptual analysis. We emphasize on the role of organizations in maintaining a work environment where university teachers’ wellbeing is prioritized and various elements such as training and support are used to help stabilizing work-life balance. The current findings can be beneficial for both scholars and decision-makers in schools and universities to enhance elements of remote work for their staff.